Outbreak of fatal mushroom poisoning with Amanita franchetii and Ramaria rufescens - Huang, Liang (BMJ Publishing Group, 2009)
Mushroom poisoning continues to occur worldwide. We report a cluster of sudden death in two villages of the Gan County, Jiangxi Province, People’s Republic of China in September 2005. Extensive investigations on the clinical presentation, epidemiological features, food and water sources have led to the identification of mushroom poisoning. Each of the 10 patients ate wild mushrooms, identified as Amanita franchetii and Ramaria rufescens, and suffered gastrointestinal symptoms prior to sudden deaths.